Electronic Patient Records to Identify Patients in the United Kingdom with Diabetic Macular Oedema Suitable for ILUVIEN® (Fluocinolone Acetonide). Issue 1 (June 2016) - Butt, Farhat; Khan, Kamron; Chaudhry, Saadia; Khan, Rehna
Abstract Introduction We describe a proactive method using electronic patient records (EPR) to identify pseudophakic patients with diabetic macular oedema (DMO) that might benefit from treatment with 0.2 µg/day fluocinolone acetonide (FAc; ILUVIEN® ) implant. Methods Our EPR audit tool (Medisoft® ) identified diabetic patients (May 2011–December 2014) with National Screening Committee-confirmed grade M1 maculopathy. Searches segmented this DMO patient population into patient groups who: (1) had received ranibizumab therapy, (2) had received ≥2 macular laser treatments, or (3) were unsuitable for macular laser or ranibizumab therapy. Pre-specified criteria identified patients insufficiently responsive to treatment, and their electronic case notes were flagged for clinicians to consider FAc, based on National Institute for Health and Care Excellence (NICE) TA301. Results Using this methodology, 138 patients with DMO were identified, of whom 87 were assigned to group 1, 32 to group 2, and 29 to group 3 (10 patients were included in both groups 2 and 3). From these, 28 different pseudophakic eyes were identified as suitable for treatment with FAc, based on insufficient response to prior treatment. Conclusion EPR audit offers a real-world methodology to efficiently identify patients that might benefit from treatment with FAc. Limitations apply, and thorough documentation of lens status and ocular comorbidities is vital; however, this approach was more rapid than prospective recruitment through the clinic. Flagging patient records using EPR audit offers a practical process for application to clinical practice, thereby optimizing patient care in line with NICE TA301 guidelines. Funding Alimera Sciences Ltd.